Biopolímeros: aplicações farmacêutica e biomédica - Trovatti, Eliane; dos Santos, Aline Martins; Amaral, André Capaldo; Meneguin, Andréia Bagliotti; Matos, Bruna Driussi Mistro; Pacheco, Guilherme; de Carvalho, Renata Aquino; Lazarini, Silmara Cristina; Cardoso, Valéria Maria de Oliveira; Lustri, Wilton Rogério; Barud, Hernane da Silva (Eclética Química, 2016)
The study and development of polymers for pharmaceutical and biomedical use has been increasing due to their peculiar properties that contribute for the improvement of the life quality, such as the polymers used in regenerative medicine and in drug release systems. The development of new polymer based materials and its composites depends on several steps, such as the synthesis approach, the extraction, the composition, the influence of their properties on the specific applications, and others. This review describes the use of conventional and new polymers with potential application in pharmaceutical and biomedical fields, highliting the properties that allow them to be useful for such pourposes.